2006
DOI: 10.1002/ijc.22217
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of carcinoma cell‐derived VEGF reduces inflammatory characteristics in xenograft carcinoma

Abstract: The stroma of carcinomas shares several characteristics with inflamed tissues including a distorted vasculature, active angiogenesis and macrophage infiltration. In addition, the tumor interstitial fluid pressure (P IF ) of the stroma is pathologically elevated. We show here that bevacizumab [rhuMab vascular endothelial growth factor (VEGF), Avastin], a monoclonal antibody to VEGF, at a dose of 5 mg/kg modulated inflammation in KAT-4 xenograft human anaplastic thyroid carcinoma tissue. At this dose, bevacizuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
60
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 51 publications
3
60
2
2
Order By: Relevance
“…Furthermore, bevacizumab significantly enhanced sensitivity to cisplatin. Bevacizumab is believed to normalize intratumoral blood vessels, which are markedly different from their counterparts in normal tissue (46). Intratumoral, neoangiogenic vessels are hyperpermeable, leading to interstitial hypertension and impaired perfusion in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, bevacizumab significantly enhanced sensitivity to cisplatin. Bevacizumab is believed to normalize intratumoral blood vessels, which are markedly different from their counterparts in normal tissue (46). Intratumoral, neoangiogenic vessels are hyperpermeable, leading to interstitial hypertension and impaired perfusion in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The increased ECV in fibromodulin-deficient carcinomas also suggests that the collagen scaffold is less stiff, allowing tumors to swell because of the high plasma protein content in the carcinoma interstitium that results from the leaky blood vessels. Indeed, treatment of KAT-4 carcinomas with a specific inhibitor of carcinoma cell-derived vascular endothelial growth factor (Bevacizumab) decreases plasma protein leakage and reduces the ECV (19). An increased hydraulic conductivity and fluid flow in carcinomas may also explain the increased efficacy of chemotherapy in KAT-4 carcinomas pretreated with Fc:T␤RII (17).…”
Section: Discussionmentioning
confidence: 99%
“…Tortuous and leaky blood vessels, and absence of lymph drainage in tumors have also been suggested to be involved in the generation of the elevated tumor IFP. Inhibition of plasma protein leakage by interfering with vascular endothelial growth factor reduces IFP in experimental carcinomas (18,19) and human rectal carcinoma (15). Little is known, however, about how the structure and composition of the ECM in the stroma influence carcinoma IFP.…”
mentioning
confidence: 99%
“…In vitro assays have also demonstrated that CAFs induce resistance to chemotherapy via secreting cytokines (16,22,23). Besides chemotherapy agents, inhibiting CAFs may also enhance the effects of bevacizumab (rhuMab VEGF, Avastin) even in bevacizumab-resistant GC cells (24), which is similar to the selective susceptibility of α-SMA-deficient vessels to bevacizumab (25). CAFs are the primarily source of VEGF, cancer epithelial cells are able to produce VEGF and the level of VEGF is increased through the cancer-stromal interaction (26).…”
Section: Discussionmentioning
confidence: 99%
“…CAFs are the primarily source of VEGF, cancer epithelial cells are able to produce VEGF and the level of VEGF is increased through the cancer-stromal interaction (26). VEGFs and their receptors have been revealed to modulate vascular permeability activity, leading to enhanced interstitial fluid pressure in the tumor stroma, which is associated with chemotherapeutic resistance (25).…”
Section: Discussionmentioning
confidence: 99%